On the Subject, Purpose and Method of Religious Education as a Practical Metaphysics - Süleyman Gümüş (Rize İlahiyat Dergisi)

(untitled)
The aim of this study is to discuss the possibility of conceiving the current science of religious education as a practical metaphysics without excluding its objectives. Contemporary science of religious education is a religious pedagogy in terms of the conditions that brought it into existence and its characteristics. Therefore, religious education activities are implemented following the religious knowledge constructed by the science of religious education within the limitations of pedagogy. And pedagogy, on the other hand, depends on the paradigm of existence, human being and behavior that finds its meaning in natural sciences such as physics and biology, human sciences, especially psychology, and educational sciences, which have been established depending on the natural state in which modernity is formed. A pedagogical approach to religion is necessarily anthropological due to the discursive characteristics of pedagogy. While it considers a specific religion and its tradition, it derives its principles from a spectrum of sciences, ranging from natural sciences to educational sciences. Religious education activities are therefore bound to a paradigm of the human being whose capabilities are determined. But, as a newly established discipline, religious education as religious pedagogy naturally does not possess a thoroughly developed theoretical framework (naẓarīyat), its principles, purposes, methods and outcomes of religious education activities have not been critically analysed. However, education is the process of becoming human, and by taking various differences in meaning into account, it means becoming a social reality, historicizing, and becoming a subject. Religious education as a practical metaphysics which is proposed to replace religous pedagogy, maintains its critical perspective and since it deals with subjectivity and the historicization of subjectivity, pedagogy can be articulated to other discourses and institutions taking into account the criteria of verification. Religious education as practical metaphysics is not obliged to derive its foundational principles from any specific science, as it’s founded on existence (fıṭrah) itself. Instead, it demands the reconsideration of the sciences in the view of potential forms of subjectivity and promotes the establishment of new scientific disciplines. The basic framework and concepts used in this study have been taken from Platonic philosophy and Foucault’s analyses. Because the contemporary educational paradigm is part of a tradition that extends from Aristotle to modern science. Besides, traditional religious thought represented by the sciences of the explication (bayān) has established strong links with Aristotelian thought via kalām. Plato's philosophy, on the other hand, presents a third theoretical (naẓarī) alternative to Aristotelian philosophy and the discipline of kalām. Plato’s allegory of the cave, which coincides with the verses that the worldly life is play and amusement finds its theoratical grounding in Foucault’s analyses on subjectivation, encompassing processes of socialization and historicization. The analysis of subjectivity enables us to perceive the human being in a holistic manner, which is reduced in the Aristotelian thought system and fragmented in the discipline of kalām, as it reveals the human existence in its most general characteristics. Religiosity in terms of identity (huwiya) is the primary characteristic of subjectivity. Religiosity in the sense of identity is the primordial attribute and the most general characteristics of subjectivity - in addition to this meaning, religiosity also signifies religious attachment. The analysis of subjectivity allows us to see the human being in a holistic manner, revealing human existence in its most general characteristics, unlike in the Aristotelian thought where it is reduced, or in the discipline of kalām where it is fragmented. The study consists of three parts in which the subject, aims and methods of religious education as a practical metaphysics have been expounded. The subject of religious education as a practical metaphysics is the most general form of human existence in the world, which is subjectivity. Its purpose is to demonstrate the process of subjectification integrated with pedagogy by scrutinizing the conditions for the formation of subjectivity. Thus, pedagogy can be conducted in harmony with the general principles of subjectification. Practical metaphysics employs the dialectical method in terms of human relation to truth, archaeology and genealogy for the analysis of subjectivity and forms of subjectivation, and any proper method for its pedagogical dimension.